Orthotopic ureterocele masquerading as a bladder tumor in a woman with pelvic pain - David D. Thiel; Steven P. Petrou; Gregory A. Broderick (International Brazilian Journal of Urology, 2005)
Single system orthotopic ureteroceles often present in adulthood are associated with characteristic radiographic findings. We present the case of a 54 year old woman with 8 months of urgency/frequency and pelvic pain that has the cystoscopic appearance of a bladder tumor. Cystoscopic images, radiographs and intraoperative photos demonstrate the work-up, evaluation, and treatment of this unique single system orthotopic ureterocele containing a calculus. This patient demonstrates the need for cystoscopy accompanied by upper tract imaging in patients with new onset pelvic pain, urgency/frequency, and frequent urinary tract infections.